Dental Abscess A diagnostic enigma (Journal of Pharmaceutical Negative Results, 2022)
Amongst the various ailments that a dentist routinely encounters, one of the most frequently presented conditions is dental abscess. Dental abscesses pertain to a broad range of diagnoses which entails periapical, periodontal, and pericoronal abscesses. Any infection in the oral cavity commonly presents with a host of the interplay of common microbial etiology and symptoms, most often with an overlapping history. This is where the diagnostic and clinical judgment skills of the dentist become the most important. Dental Abscess is one of the most common dental ailments which is unfortunately often misdiagnosed and underestimated. An abscess if neglected may sometimes even turn fatal and can have life-threatening consequences. It is therefore of utmost importance that the proper source of infection be traced so that since the etiological factor is controlled, the results are longstanding without any recurrence of the same. There has been ample support in previous literature about the fatal outcomes of a dental abscess which most often leads to significant morbidity and mortality. The fatality in the dental abscess is attributed to either the spread of infection either into the deep neck fascia or into the intracranial sinuses. As for the treatment protocol for the treatment of dental abscess, Incision and drainage still remain the first and foremost treatment modality for any abscess which may be sometimes accompanied by a supportive antimicrobial regimen. It is therefore imperative that clinicians must be aware of the source of infection through adequate history taking and clinical examination so as to avoid recurrence of the disease.